Prevalence of Hypodontia in 10- to 14-Year-Olds Seeking Orthodontic Treatment at a Group of Clinics in Puerto Rico - Pagán, Grace J.; Oliva, Jazmin; Cuadrado, Lumarie; Rivas-Tumanyan, Sonia; Elías-Boneta, Augusto R. (Puerto Rico Health Sciences Journal, 2014)
Objective: To estimate the prevalence of hypodontia in a group of 10- to 14-year olds from a group of orthodontic clinics in Puerto Rico. Methods: A cross sectional study was conducted to estimate the prevalence of hypodontia in 10- to 14-year-olds from orthodontic clinics located in each of 9 regions (as determined by the government-run health insurance program, Reforma) in Puerto Rico. A total of 1,911 patients, ranging in age from 10 to 14 years, were evaluated using patient charts covering from May 2004 through June of that same year. A logistic regression model was done to evaluate the relation between the prevalence of hypodontia in the study group and clinic location, gender, and age; a 5% significance level was used. Results: The overall weighted prevalence of hypodontia was 6.02%. Females showed a higher weighted prevalence of hypodontia than did males (7.02% vs. 4.72%, respectively: p=0.06). The prevalence also varied by geographic region, ranging from 3.21% at the San Juan clinic to 10.68% at the Aibonito clinic (p=0.01). The most prevalent missing teeth were the maxillary lateral incisors, followed by the lower second premolars (1.9%). Conclusion: The prevalence of hypodontia in Puerto Rico was 6.02%. Females presented a higher prevalence of hypodontia than did males. Each of the clinics in Fajardo, Bayamón, San Juan, and Guayama had a lower prevalence of hypodontia than the Aibonito clinic did. The tooth most frequently missing in the study group was the maxillary right lateral incisor.